Analisis Penerapan Nilai-nilai Kewarganegaraan dalam Pembelajaran PPKn pada Kurikulum Merdeka - Nabilaqistynst Nabilaqistynst; Syamzaimar Syamzaimar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Merdeka Curriculum, as a new educational policy in Indonesia, emphasizes the cultivation of the Pancasila Student Profile, which is rich in citizenship values. This study aims to analyze the application of citizenship values in Pancasila and Civic Education (PPKn) learning within the framework of the Merdeka Curriculum at the high school level. This research employs a qualitative descriptive method, collecting data through classroom observations, semi-structured interviews with PPKn teachers, and analysis of teaching modules and project-based learning documents (P5). The findings indicate that the application of citizenship values is primarily integrated through Project-Based Learning to Strengthen the Pancasila Student Profile (P5). Values such as mutual cooperation (gotong royong), critical reasoning (bernalar kritis), and global diversity (berkebinekaan global) are the most frequently emphasized. However, teachers face challenges, including the need to adapt pedagogical approaches, difficulties in assessing value-based outcomes authentically, and a lack of specific reference materials aligned with the new curriculum. The implication of this research is the urgent need for structured professional development for teachers and the development of comprehensive teaching guides to ensure the effective and standardized implementation of citizenship values in PPKn learning across all educational units.